Entre o corte da cerca e a teia da rede: desafios do MST na luta pela reforma agrária no Brasil - Silveira, Cássio Rodrigues da (2015)
We aim in this thesis to analyze aspects of the transformations occurred in the MST, Movimento dos Trabalhadores Rurais Sem Terra (in free translation: Rural Workers Landless Movement), from 1981 until January 2015, through its publications. We made it clear that what is presented here is a set of representations as this concept is defined by Roger Chartier of the movement about issues which we choose as relevant to understanding its dynamics in time. The central point of documentation used in the work is the Jornal dos Trabalhadores Rurais Sem Terra (in free translation: Journal of Landless Rural Workers), which has its beginning, even as a report, before the official foundation of the MST in 1984, but were also used other informational and training publications, besides its content site, which came into being in 1996. As the movement developed into a trends accent period of modernity, such as individualism, consumerism and social breakdown, trying to understand, through research, what were the impacts this situation on our subject. Therefore, the initial part of the thesis strives to clarify the main characteristics of temporality issue that could influence the MST. We follow their perceptions of land reform, the formation of their members both with regard to some forms as the ideological content its relationship with the state and the issue of violence as it is felt and performed by social subjects we set ourselves the study. In its quest to establish new relations in the field, the movement, since its inception, realized that it would be very difficult within capitalist relations, particularly in its neoliberal version, and took a discourse of class, with strong revolutionary content. The MST, thereby, with rare exceptions, always understood that the changes sought would be consolidated see the size of its force to generate them through the struggle. Since the 1980s and especially from the 90s, the movement gradually alia increasingly complex network of individuals on the planet, designated by the general term alterglobalisation which currently come together around a common theme: another world is possible . The limits and scope of this statement, as well as the ways in which the MST seeks to enter this field of struggle, are also analyzed in the work.